Some remarks on the strictly positive measures (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
It is shown that if $K$ is a Grothendieck compact space, then $K$ admits a strictly positive measure if and only if there exists a linear bounded one-to-one operator $T:C(K) → c_0(Γ)$